MENINGKATAN KEMAMPUAN MENYIMAK ANAK USIA 4-5 TAHUN MELALUI METODE BERCERITA DENGAN BIG BOOK DI TAMAN KANAK-KANAK AR-RAASYIDIN PARIT AMAN KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Julia, Julia; Zulkifli N, Zulkifli N; Nurlita, Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this study is the lack of ability of the child in listening skills, some children may not be able to mimic back 3-4 order of words, some children may not be able to sort the contents of the picture and tells a simple, some children may not be able to retell the story in a simple , Therefore, efforts need to be able to improve listening skills of children is through storytelling with a big book. The purpose of this study was to determine the increase listening skills of children through storytelling with big method book and to know the high increase occurred. This research is a classroom action research conducted in two (2) cycles. Data collection tool used in this study is in the form of sheets of observation and research subject is a group consisting of 8 boys and 7 girls. The results showed an increase from cycle I to cycle II. Improvement occurred, ie from before the action to the first cycle of 34.58%, the first cycle to the second cycle of 35.43%, and increased from the prior cycle to cycle II of 82.27%. From these results obtained conclusions that through storytelling with big book can improve listening skills of children at Tk Ar-Raasyidin Parit Aman District of Bangko Rokan Hilir.Keywords: Listening, storytelling with a big book